Unlocking the talus by eversion limits medial ankle injury risk during external rotation. Issue 13 (15th October 2015) - Button, Keith D.; Wei, Feng; Haut, Roger C.
Abstract: Eversion prior to excessive external foot rotation has been shown to predispose the anterior tibiofibular ligament (ATiFL) to failure, yet protect the anterior deltoid ligament (ADL) from failure despite high levels of foot rotation. The purpose of the current study was to measure the rotations of both the subtalar and talocrural joints during foot external rotation at sub-failure levels in either a neutral or a pre-everted position as a first step towards understanding the mechanisms of injury in previous studies. Fourteen (seven pairs) cadaver lower extremities were externally rotated 20° in either a pre-everted or neutral configuration, without producing injury. Motion capture was performed to track the tibia, talus, and calcaneus motions, and a joint coordinate system was used to analyze motions of the two joints. While talocrural joint rotation was greater in the neutral ankle (13.3±2.0° versus 10.5±2.7°, p =0.006), subtalar joint rotation was greater in the pre-everted ankle (2.4±1.9° versus 1.1±1.0°, p =0.014). Overall, the talocrural joint rotated more than the subtalar joint (11.9±2.8° versus 1.8±1.6°, p <0.001). It was proposed that the calcaneus and talus 'lock' in a neutral position, but 'unlock' when the ankle is everted prior to rotation. This locking/unlocking mechanism could be responsible for an increased subtalar rotation, but decreased talocrural rotation when the ankle is pre-everted, protecting the ADL from failure. This study may provide information valuable to the study of external rotation kinematics and injury risk.